Intervention programs for children and parents experiencing parental cancer: a scoping review - Lomba, Maria de Lurdes Lopes de Freitas (2023)
Purpose: Parental cancer comprises the experience of cancer at an early age of adulthood, in people with dependent children, representing a significant stressor for patients and children. This study aims to map intervention programs to children, adolescents and parents, or binomial (cancer patients and their children) experiencing parental cancer; identify the typology of interventions proposed in the programs; and identify and describe the intervention programs that are developed by different health professionals, such as nurses. Methods: A scoping review was carried out in accordance with the methodology recommended by the JBI and the Preferred Reporting Items for Systematic Reviews - Scoping Reviews. The eligibility criteria to select the studies were define based on Population, Concept and Context. Population includes children and adolescents, up to 19 years old, with at least one of the parents diagnosed with cancer, regardless of type and stage of cancer, the parents (oncology patients), and the binomial. Concept includes intervention programs for the study population, regardless of type of interventions implemented (educational, psychoeducational and psychosocial), developed by health professionals. 1 de 7 02/10/2022, 19:52 Submission Completed https://stti.confex.com/stti/bc23/popsci/papers/confirmation.cgi?step=... Intervention programs should aim to promote children's and adolescents' adjustment to parental cancer and meet the needs of parents. All intervention contexts were considered, without any limitation. Results: The database search identified 813 records. The selection process resulted in the inclusion of 16 studies in this review, carried out between 1992 and 2020 in eight different countries. After a comprehensive analysis of the selected studies, 29 intervention programs were identified, 13 of which were aimed at the binomial, 11 at children and adolescents, and 5 at parents. Of the 29 programs identified, 10 do not specify the typology of proposed interventions, 9 refer to psychoeducational interventions, 7 are educational interventions and 3 are psychosocial interventions. Only four of the programs identified were health professionals in the team: nurses, psychologists, and psychologists and doctors. The description of the interventions is identified in 3 of the programs aimed at the binomial and in 1 of the programs aimed at children and adolescents Conclusion: It was concluded that programs aimed at the binomial and with psychoeducational interventions are the most used, with those aimed at parents (oncology patients) being the least mentioned. The programs that integrate nurses into the team are scarce, highlighting the need for greater investment by this professional class in the area of parental cancer. Although some programs identify theoretical models underlying intervention programs, only 1 integrates a model related to parental cancer. None of the programs were implemented in health institutions, suggesting future development of intervention programs in the hospital context. The results of this scoping review synthesize knowledge about existing intervention programs, enabling its implementation in clinical practice for families who experience parental cancer, meeting the needs of children, adolescents and their parents. This review highlights existing gaps in the area, suggesting the development of new studies, namely assessment of the effectiveness of intervention programs aimed at all stakeholders (parents and children).